If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (u + 7)(u + 8) = 0 Reorder the terms: (7 + u)(u + 8) = 0 Reorder the terms: (7 + u)(8 + u) = 0 Multiply (7 + u) * (8 + u) (7(8 + u) + u(8 + u)) = 0 ((8 * 7 + u * 7) + u(8 + u)) = 0 ((56 + 7u) + u(8 + u)) = 0 (56 + 7u + (8 * u + u * u)) = 0 (56 + 7u + (8u + u2)) = 0 Combine like terms: 7u + 8u = 15u (56 + 15u + u2) = 0 Solving 56 + 15u + u2 = 0 Solving for variable 'u'. Factor a trinomial. (8 + u)(7 + u) = 0Subproblem 1
Set the factor '(8 + u)' equal to zero and attempt to solve: Simplifying 8 + u = 0 Solving 8 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + u = 0 + -8 Combine like terms: 8 + -8 = 0 0 + u = 0 + -8 u = 0 + -8 Combine like terms: 0 + -8 = -8 u = -8 Simplifying u = -8Subproblem 2
Set the factor '(7 + u)' equal to zero and attempt to solve: Simplifying 7 + u = 0 Solving 7 + u = 0 Move all terms containing u to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + u = 0 + -7 Combine like terms: 7 + -7 = 0 0 + u = 0 + -7 u = 0 + -7 Combine like terms: 0 + -7 = -7 u = -7 Simplifying u = -7Solution
u = {-8, -7}
| 3/4*2.10 | | 7(-6-2b)=6-8b | | 20-43=4(x-1)-7 | | 0.6(6e+9f-21g)-7f= | | (-3)/(-4) | | z=13+2(x+y)forx | | 12c=156 | | 11-19c=-18c-19+c | | -14-3m=-m+10 | | -10=-9q+7 | | 10+5f=9f-10 | | 6z-1=3+4z+6 | | (9n+4)+(9n+4)=180 | | 7n+2=-2+8n | | -u=-2u-7 | | 180(n-2)=5400 | | 5w-3=4w | | -9k+5=-10k-4 | | -9k+5=-10j-4 | | -2s-6=-s | | -34=8x-5(1-7x) | | 4j=5j-7 | | 4x+8=12x-12 | | 3g=-7+4g | | 9(t-5)+6t=5(3t+4)-10 | | m=-0.4n+28 | | y+y-y-y+y-1=18 | | -93-4v=-10v+3 | | 2x^4-9x^2-16x=0 | | 3h+3h-6h+2j-2=12 | | 2x^4-9x^2-16=0 | | 18j+2j-10j-5j-4j=16 |